Do Poor Citizens Benefit from Mega-Events? São Paulo's Street Vendors and the 2014 FIFA World Cup. (4th September 2018) - Hummel, Calla
Abstract: International mega-events inject millions of dollars into host countries' economies, yet few studies assess which citizens benefit from events and which do not. Governments justify their bids for mega-events by arguing that infrastructure projects, event-related jobs, and tourist spending benefit many citizens. However, researchers find mixed impacts on host economies and the average citizen. Scholars and activists argue that a few businesses benefit while high prices and event-specific laws exclude poor citizens. Under what conditions do poor citizens benefit from mega-events? This article analyzes original interview, survey, and participant observation data on street vendors in São Paulo, Brazil during the 2014 FIFA World Cup. The project finds that most street vendors lost money, while a minority made record profits. Those who benefited from the event used brokers, bribes, and pockets of forbearance to circumvent FIFA's exclusionary rules.